Experiences integrating teleworking tools in faceto-face teaching: academic results - Vereda-Alonso, Cristina; Cerrillo-González, María del Mar; Gómez-Lahoz, César; Villén-Guzmán, María Dolores; Paz-García, Juan Manuel; Vereda-Alonso, Carlos (IATED Academy, 2024)
An Educational Innovation Project is currently underway at the University of Malaga. The primary goal of the project is to enhance the skills acquired in synchronous online teaching during the COVID-19 confinement, with a specific emphasis on their application in the context of teleworking, which is increasingly becoming established in the business world. The experience is implemented in three subjects across various undergraduate and master's programs: the fourth-year subject “Treatment of Contaminated Soil” in the Chemical Engineering degree, the first-year subject “Mass Exchange Network for Pollution Prevention” in the Master's degree in Chemical Engineering, and the third-year subject “Psycholinguistics Applied to the Study of the English Language” in the English Studies degree.
Acceso libre al abstract en https://library.iated.org/view/VEREDAALONSO2024EXP2
Keywords: Tecnología educativa; Enseñanza - Innovaciones; Synchronous online presentation; Microsoft Teams; Challenges of moderating